2011
DOI: 10.4028/www.scientific.net/kem.464.151
|View full text |Cite
|
Sign up to set email alerts
|

Image Segmentation Based on Improved Adaptive Genetic Algorithm

Abstract: Using computer vision technology to accurately identify weeds and crops, positioning weed and spraying of weedcide has become a hotspot of precision agriculture. To determine the optimal threshold in image automatic segmentation and solve one-dimensional histogram without obvious peak and valley distribution, image segmentation method based on two-dimensional histogram and Improved Adaptive Genetic Algorithm is proposed. In the method, the genetic algorithm carries on the global optimization to get the thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 3 publications
0
32
0
Order By: Relevance
“…[160][161][162] Aer modication, they become soluble in different solvents, as well as contain functional groups, which turn them into a multidisciplinary materials in other applications. The functionalization by chemical oxidation of CNTs is the most commonly used method, which breaks the sp 2 hybrid carbon bonds on the sidewalls, and attaches carboxyl/hydroxyl groups to the CNTs.…”
Section: 146-159mentioning
confidence: 99%
“…[160][161][162] Aer modication, they become soluble in different solvents, as well as contain functional groups, which turn them into a multidisciplinary materials in other applications. The functionalization by chemical oxidation of CNTs is the most commonly used method, which breaks the sp 2 hybrid carbon bonds on the sidewalls, and attaches carboxyl/hydroxyl groups to the CNTs.…”
Section: 146-159mentioning
confidence: 99%
“…This solution was filtered through a PTFE membrane (0.2µm) and dried in a vacuum oven. In the second step, carboxylic acid groups were activated through refluxing with thionyl chloride with a catalytic quantity of N,N-dimethylformamide for 24 h. 21,25,26 The excess of thionyl chloride was removed by vapour distillation under reduced pressure. The product was washed with dichloromethane and dried in a vacuum oven.…”
Section: Functionalization Of Nanotubesmentioning
confidence: 99%
“…It is also known that different types of functionalization process lead to good dispersibility in organic solvents. 19,20,21 The objective of this research is the functionalization of MWCNT in order to incorporate in OPV cells, which is attractive to produce low-cost energy devices. Many research reports described that the carboxylic acid functionalized MWCNT (O-MWCNT) resulted in improved thin film deposition compared with pristine MWCNT and that enhanced the power conversion efficiency of OPV cells.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of GO and the graphene as used in the previous work, this work focuses on using amine‐functionalized graphene nanoplatelets since they are water‐dispersible without the aid of surfactants, thus enabling facile fabrication of composite electrospun mats based on water‐soluble PVA. The amine group has high chemical reactivity and can readily react with other chemicals . It has also been reported that the amine group can enhance the dye adsorption of particular adsorbents under mild conditions (ca.…”
Section: Introductionmentioning
confidence: 99%